hsBAFF-upregulated intracellular free Ca2+ homeostasis regulates ERK1/2 activity and cell proliferation in B cells in vitro - Liang, J. Q; Zhang, W; Wen, L; Gao, W; Zhang, S. Q; Chen, L (Physiological research, 2009)
We studied hsBAFF activity in in vitro mouse splenic B cells. hsBAFF effects on intracellular free Ca2+ concentration ([Ca2+]i) were assayed, using a laser scanning confocal microscope with fluorescent probe, Fluo-3/AM. We showed that treatment of B cells with 0.5-5 µg/ml hsBAFF resulted in significantly higher [Ca2+]i levels in a dose-dependent fashion at 12 and 24 h, respectively (p<0.05 or p<0.01 vs. control). Furthermore, we noticed that 2.5 µg/ml hsBAFF-treated cells were significantly resistant to decrease of cellular viability induced by thapsigargin (Tg), an endoplasmic reticulum (ER) Ca2+-ATPase inhibitor (p<0.05 hsBAFF plus Tg group vs. Tg group). Thus hsBAFF may promote B cell survival by direct upregulation of [Ca2+]i physiological homeostasis contributing to prevention of [Ca2+]i dysfunction. Using immunocytochemistry and Western blot analysis, we found that the activation of ERK1/2 due to hsBAFF was triggered by a [Ca2+]i-dependent pathway, leading to elevation of B cell proliferation. This is supported by the findings that intracellular Ca2+ chelator BAPTA/AM attenuated phosphorylated ERK1/2 expression and cell proliferation in hsBAFF-stimulated B cells. hsBAFF-stimulated B cell proliferation was obviously reduced by mitogen extracellular kinase 1/2 (MEK1/2, upstream of ERK1/2) inhibitor U0126. Taken together, the main finding of this study is that hsBAFF elicits higher but homeostatic [Ca2+]i levels, which regulates ERK1/2 activity and cell proliferation in in vitro B cells
Keywords: mitogenem aktivovaná proteinkinasa 3; financování organizované; Mice, Inbred ICR; kultivované buňky; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Protein Kinase Inhibitors; Egtazic Acid; Phosphorylation; Time Factors; EGTA; Mitogen-Activated Protein Kinase 3; vápník; butadieny; chelátory; Mice; Cell Proliferation; faktor aktivující B-buňky; mitogenem aktivovaná proteinkinasa 1; Calcium; Cells, Cultured; B-lymfocyty; Financing, Organized; Mitogen-Activated Protein Kinase 1; sarkoplazmatická Ca2+-ATPáza; zvířata; B-Lymphocytes; Humans; myši inbrední ICR; thapsigargin; Sarcoplasmic Reticulum Calcium-Transporting ATPases; homeostáza; Nitriles; Butadienes; časové faktory; viabilita buněk; B-Cell Activating Factor; Cell Survival; myši; proliferace buněk; Chelating Agents; inhibitory proteinkinas; fosforylace; Homeostasis; nitrily; Thapsigargin; Enzyme Inhibitors; lidé; inhibitory enzymů; Animals